Association between cardiometabolic index and overactive bladder in adult American women: A cross-sectional study - Junhua Li; Min He; Yu Zhou (PLoS ONE, 2025)
Background Overactive bladder (OAB) is a common disorder, particularly in women, and its symptoms, including urgency, frequency, and nocturia, can significantly affect quality of life. The cardiometabolic index (CMI) is a novel metabolic risk indicator that has been receiving more attention lately. This study investigated the association between CMI and OAB in adult women. Methods A cross-sectional analysis was performed using data from the National Health and Nutrition Examination Survey (NHANES) covering the years 2007 to 2018, including 6323 female participants. CMI was calculated based on waist-to-height ratio, triglyceride, and HDL cholesterol levels, while OAB was assessed using the overactive bladder symptom score (OABSS). The association between CMI and OAB was evaluated through multivariate logistic regression, generalized additive models (GAM), smoothing curve fitting, and subgroup analysis. We finally included male participants for sensitivity analysis. Results A significant positive association was found between female CMI and OAB prevalence (OR = 1.46, 95% CI: 1.29–1.65). When compared to the lowest CMI quartile (Q1), women in the highest CMI quartile were 70% more likely to have OAB (OR = 1.70, 95% CI: 1.42–2.04). Smoothed curve fitting analysis showed a linear association between CMI and OAB. Subgroup analysis revealed that the association between CMI and OAB was stronger in women aged 20–50 years as well as in women without hypertension. Sensitivity analysis confirmed the robustness of our result. Conclusion CMI was significantly and positively associated with the prevalence of OAB, especially in women aged 20–50 years without hypertension. This finding provides a new perspective on metabolic risk management and may contribute to the early prevention and improvement of bladder function in women.